Dialectical tensions in the jurisprudence of the International Criminal Court : fair process, the demands for justice and the expectations of the international community - Van der Burg, Anthea (Stellenbosch : Stellenbosch University, 2020)
Thesis (LLD)--Stellenbosch University, 2020.